2010
DOI: 10.2174/138920210791233108
|View full text |Cite
|
Sign up to set email alerts
|

The Human Glioma-Associated Oncogene Homolog 1 (GLI1) Family of Transcription Factors in Gene Regulation and Diseases

Abstract: Sonic hedgehog (Shh) signaling is critically important for embryogenesis and other cellular processes in which GLI transcription factors mediate the terminal effects of the pathway. GLI1, in particular, plays a significant role in human cancers. Consequently, GLI1 and its upstream positive regulator Smoothened (SMO) are important targets of anti-cancer therapy and several SMO-targeted small molecule inhibitors are being evaluated clinically. Emerging exciting evidence reveals a high level of complexity that li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 66 publications
1
52
0
Order By: Relevance
“…As expected, the transcripts of several Gli1 target genes, including endogenous GLI1 , PTCH1 , IGFBP6 , CCND1 , BCL2 , and SNAIL1 (32), were lower in MIA PaCa-2 cells stably expressing R597K-mutant Gli1 (MIA/Gli1RK cells) than in MIA PaCa-2 cells expressing wild-type Gli1 (MIA/Gli1WT cells) (Figure 3A and Supplemental Figure 3A). Consistently, results from a transient reporter assay in 293T cells using Gli binding sequence (GliBS) reporter plasmid (31) confirmed that wild-type Gli1 harbored stronger transcriptional activity compared with R597K-mutant Gli1 (Supplemental Figure 3B).…”
Section: Resultssupporting
confidence: 71%
“…As expected, the transcripts of several Gli1 target genes, including endogenous GLI1 , PTCH1 , IGFBP6 , CCND1 , BCL2 , and SNAIL1 (32), were lower in MIA PaCa-2 cells stably expressing R597K-mutant Gli1 (MIA/Gli1RK cells) than in MIA PaCa-2 cells expressing wild-type Gli1 (MIA/Gli1WT cells) (Figure 3A and Supplemental Figure 3A). Consistently, results from a transient reporter assay in 293T cells using Gli binding sequence (GliBS) reporter plasmid (31) confirmed that wild-type Gli1 harbored stronger transcriptional activity compared with R597K-mutant Gli1 (Supplemental Figure 3B).…”
Section: Resultssupporting
confidence: 71%
“…The following known Gli-binding sites were used in the search parameters: GAGCAGCCA, GACGACCCC, GGCCCCCCA, GACCGCCCC, AACCAACCCC, GTCCTCCCA, GACCAC CCA (10), GAACACCCA, CACCACCCA and GACCACCAA (11). A pairwise BLAST (basic local alignment search tool, bl2seq, http://blast.ncbi.nlm.nih.gov/Blast.cgi) was performed to compare the promoter region with each GBS.…”
Section: Methodsmentioning
confidence: 99%
“…GLI1 and GLI3 are mediators of the SHH pathway, which has an effect on the early development of the central nervous system (36). In addition, SHH-GLI1 is involved in the self-renewal of cancer stem cells (37).…”
Section: Discussionmentioning
confidence: 99%